Mapping the evolution of corporate social responsibility – insights from the Finnish forest industry. (2nd January 2016) - Pätäri, S.; Sandström, J.; Puumalainen, K.; Tuppura, A.
Abstract : The number of companies engaging in corporate social responsibility (CSR) has increased significantly. However, the ways in which CSR is understood and practised are strongly dependent on contextual characteristics, such as the industry. The objective of this study is to map the evolution of CSR in the Finnish forest industry. Drawing from thematic interviews with selected participants and from environmental and CSR reports, the underlying factors and stakeholders that have influenced the development of CSR at different times are identified. The findings indicate that there are four main areas in the evolution of CSR, during which the emphasis of different elements of CSR has varied. The stakeholder groups driving CSR have turned from authorities and trade unions to local communities, non-governmental organisations and customers. Managers may find the results useful when analysing the development of CSR practices and the role of stakeholders in this development.